NEBIVOLOL - ESPECIAL BETA-ADRENOBLOCKER - T. Műnzel; T. Gori (Столичная издательская компания, 2016)
Translation and publication of the paper is performed with the permission of American College of Cardiology and under control of Society of Cardiology of the Russian Federation. Paper Műnzel T, Gori T. Nebivolol. The somewhat-different β-adrenergic receptor blocker was initially published in J Am Coll Cardiol 2009;54:1491-9 © 2009 by the American College of Cardiology Foundation.